2020
DOI: 10.1371/journal.pone.0232461
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of AST-120 that suppresses indole signaling in Escherichia coli, which attenuates drug tolerance and virulence

Abstract: AST-120 (Kremezin) is used to treat progressive chronic kidney disease (CKD) by adsorbing uremic toxin precursors produced by gut microbiota, such as indole and phenols. In this study, we propose that AST-120 reduces indole level, consequently suppresses indole effects on induction of drug tolerance and virulence in Escherichia coli including enterohaemorrhagic strains. In experiments, AST-120 adsorbed both indole and tryptophan, a precursor of indole production, and led to decreased expression of acrD and mdt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…It decreases the production of indoxyl sulfate, a uremic toxin derived from indole produced by some kinds of enteric bacteria [ 19 ]. In addition to its role in CKD treatment, we recently found that AST-120 decreased drug tolerance and virulence of E. coli , including enterohaemorrhagic E. coli [ 20 ]. Here, we propose another potential benefit of AST-120 in reducing the cytotoxicity of P. aeruginosa by adsorbing phenazines including pyocyanin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It decreases the production of indoxyl sulfate, a uremic toxin derived from indole produced by some kinds of enteric bacteria [ 19 ]. In addition to its role in CKD treatment, we recently found that AST-120 decreased drug tolerance and virulence of E. coli , including enterohaemorrhagic E. coli [ 20 ]. Here, we propose another potential benefit of AST-120 in reducing the cytotoxicity of P. aeruginosa by adsorbing phenazines including pyocyanin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its efficacy in treating CKD, we previously found that indole induced drug tolerance and virulence in Escherichia coli including enterohaemorrhagic E. coli , and AST-120 eliminated these effects by adsorbing indole. Thus, AST-120 reduces drug tolerance and virulence in E. coli [ 20 ]. AST-120 can also adsorb some other small-sized molecules that have aromatic ring structures in addition to indole [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gel was electroblotted onto a polyvinylidene fluoride (PVDF) membrane (Bio-Rad Laboratories, Hercules, CA, United States). EspA, EspB and VSVG-tagged FliC were detected with EspA antiserum, EspB antiserum 42 , VSVG antibody (Sigma-Aldrich Co. LLC., St. Louis, MO, United States), an anti-rabbit horseradish peroxidase-conjugated immunoglobulin G (IgG) secondary antibody (Sigma-Aldrich Co.…”
Section: Methodsmentioning
confidence: 99%
“…This leads to an increase in the antibiotic tolerance in E. coli , including EHEC, and the production of proteins from the type III secretion system, which are required for virulence of EHEC [ 89 , 90 , 91 ]. AST-120 was shown to abolish the effect of indole on the induction of drug tolerance and virulence by adsorbing the indole signal [ 92 ]. This study suggested a potential application of AST-120 in antibacterial chemotherapy.…”
Section: Other Considerable Mechanisms; Sequestration Of Signal Anmentioning
confidence: 99%
“… ArsR Binding to target DNAs [ 82 ] Flavonoids HsrA Binding to target DNAs [ 85 ] NSC48630, etc. PhoP Binding to target DNAs [ 86 ] E12.1 peptide VanR Binding to target DNAs [ 87 ] Other inhibitors AST-120 - Indole signaling [ 92 ] COM-blockers - CSP activation and export [ 96 ] DADMe-Immucillin As - AI-2 signal generation [ 98 ] …”
Section: Table A1mentioning
confidence: 99%